2010
DOI: 10.1038/gene.2010.10
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 locus in inflammatory bowel disease and multiple sclerosis susceptibility

Abstract: STAT3 (signal transducer and activator of transcription 3) signaling is a critical component of Th17-dependent autoimmune processes. Genome-wide association studies (GWAS) have revealed the role of the STAT3 gene in inflammatory bowel disease (IBD) susceptibility, although confirmation in clinical subphenotypes is warranted. Mice with targeted deletion of Stat3 in T cells are resistant to experimental autoimmune encephalomyelitis, which is a multiple sclerosis (MS) model. Moreover, increased phosphorylated STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 39 publications
(33 reference statements)
3
47
0
Order By: Relevance
“…Several studies indicate that STAT3 activation plays distinctly different roles in innate and acquired immune responses in colitis: activation of STAT3 in innate immune cells enhances mucosal barrier function, whereas STAT3 activation in T-cells exacerbates colitis (Lovato et al, 2003;Musso et al, 2005). A number of studies also suggest that polymorphisms of STAT3 are associated with susceptibility to CD or UC in some population cohorts (Franke et al, 2008;Sato et al, 2009;Cenit et al, 2010;Ferguson et al, 2010;Peter et al, 2011;Polgar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that STAT3 activation plays distinctly different roles in innate and acquired immune responses in colitis: activation of STAT3 in innate immune cells enhances mucosal barrier function, whereas STAT3 activation in T-cells exacerbates colitis (Lovato et al, 2003;Musso et al, 2005). A number of studies also suggest that polymorphisms of STAT3 are associated with susceptibility to CD or UC in some population cohorts (Franke et al, 2008;Sato et al, 2009;Cenit et al, 2010;Ferguson et al, 2010;Peter et al, 2011;Polgar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a genome-wide association study, Barrett et al (2008) reported that the STAT3 locus is significantly associated with susceptibility to CD. Since then, a number of studies demonstrated that STAT3 polymorphisms are associated with UC as well as CD, but the results were not consistent in different population cohorts (Franke et al, 2008;Sato et al, 2009;Cenit et al, 2010;Ferguson et al, 2010;Peter et al, 2011;Polgar et al, 2012). Therefore, in this study, we analyzed the association between UC and two STAT3 polymorphisms (rs2293152 and rs4796793) in the Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest and some concerns the paper by Cénit et al 1 in the current issue of Genes and Immunity, regarding the effect of signal transducer and activator of transcription 3 (STAT3) locus in autoimmune diseases. In brief, Cénit et al…”
mentioning
confidence: 98%
“…The meta-analysis by De Jager et al, 2 which included two genome-wide studies on MS, 3,4 observed an initial association with rs2293152 that could not be replicated by them in an independent cohort. Simultaneously to the publication of our work in Genes and Immunity (Epub 2010 Mar 4), 1 another article dealing with the association of STAT3 polymorphisms with MS (Am J Hum Genet 2010 Feb 12) was published by Jakkula et al 5 This is, to the best of our knowledge, the only report showing an association of the STAT3 gene with MS. Although we also studied the STAT3-rs744166 polymorphism, no evidence of association with MS was detected in our cohorts.…”
mentioning
confidence: 98%
“…First, the Introduction of our paper 1 indicates the selection basis of the single-nucleotide polymorphisms genotyped: 'Two of them were previously associated with IBD: rs744166y and rs12948909. The other two were analyzed on the basis of their suggestive associations with more than one disease in the publicly available data of the GWAS performed by the Wellcome Trust Case-Control Consortium, although they did not exceed the threshold of statistical significance.'…”
mentioning
confidence: 99%